Znanja, stavovi i praksa roditelja o upotrebi antibiotika kod dece: razlike između urbanih i ruralnih sredina u Republici Srpskoj - Mijović, Biljana P; Aćimović, Jela; Đaković Dević, Jelena; Kralj, Julija; Joksimović, Bojan; Lučić Samardžija, Vesna; Đermanovic, Mirjana; Vujić Aleksić, Vesna; Zeljković, Branislav; Perić Simić, Snežana (Scripta Medica, 2022)
Background/Aim: Antibiotic use and resistance represent a growing public health issue, with a specific risk of uncontrolled use of antibiotics in children. The aim of the study was to examine differences in parental knowledge, attitudes and practices about antibiotic use in children between urban and rural areas of the Republic of Srpska.Methods: A cross-sectional study was conducted among 1459 parents of children under 6 years of age, out of which 1201 (82.3 %) lived in urban areas while 258 (17.7 %) lived in rural areas. The research is conducted among parents who brought their children to the selected primary healthcare centres and among parents of children in preschool institutions. Results: The majority of respondents (98.4 %) state that doctors are their main source of information. Only 61.2 % of respondents precisely know which drug is an antibiotic when offered different drugs and respondents from rural areas (54.3 %) more often (p = 0.012) gave more accurate answers when compared to respondents from urban areas (37.3 %). Among parents, 86 % agree with the statement that improper use of antibiotics reduces their effectiveness and leads to bacterial resistance, regardless of groups. More than a half of respondents (52.4 %) do not think that children with flu or common cold symptoms recover faster when they receive antibiotics, significantly more respondents from urban areas (p = 0.001). Respondents from rural areas significantly more often believe that antibiotics can produce harmful effects compared to respondents from urban areas (p = 0.049). Respondents from rural areas significantly more often think that antibiotic use can prevent complications caused by inflammation of the upper respiratory tract (p = 0.006). Parents from rural areas give their children antibiotics without a paediatrician’s recommendation significantly more often (4.3 %) compared to respondents from urban areas (0.6 %) (p < 0.001).Conclusion: There are differences in parental knowledge, attitudes and practices regarding antibiotic use and antimicrobial resistance among parents in rural and urban areas. There is need for additional education of parents and for greater engagement of paediatricians in providing guidance and explanations regarding the use of antibiotics.
Keywords: propisivanje antibiotika; antimikrobna rezistencija; znanje; stavovi; ponašanje